Membangun Aplikasi Pencatatan SPP Sekolah Berbasis Web: Studi Kasus pada SMA Darul Hikmah Bojongsoang - Robul Gunawan; Novita Anggraini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This Final Project aims to build a Desktop-based SPP Recording Application, which is made as a consideration in facilitating the Financial Administration Section to record SPP. This Desktop-based School Tuition Application contains school tuition recording data consisting of Student Data, Class Data, Payments and Reports. This data by SMA Darul Hikmah Bojongsoang can be used as well as possible to facilitate school performance quickly and efficiently. The research method that the author uses is the observation method, interviews, literature, and the waterfall method as a system development method. With this Desktop-based school tuition application, it is hoped that it will provide convenience to the Financial Staff in carrying out their performance. The system used in making this application is the HTML, CSS and MySQL programming languages so that the display is more attractive and responsive. So that it can be utilized by Financial Staff who want to do their job easily at SMA Darul Hikmah Bojongsoang. Furthermore, with the Desktop-Based School SPP Application, errors both in Student Data Collection for recording and doing monthly reports will be easily corrected.